Pengaruh Brand Image dan Store Atmosphere Terhadap Keputusan Pembelian Pada Konsumen Badan Usaha Milik Desa (BUMDES) Mart Banjaran - Eli Achmad Mahiri (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This research was conducted at BUMDES Mart Banjaran Majalengka and aims to determine how the influence of Brand Image and Store Atmosphere on Purchasing Decisions of BUMDes Mart Banjaran consumers in order to increase the competitiveness of rural companies in the era of globalization. The population in this study is the infinite population and the sampling technique used. in this study is a non probability sampling with incidental sampling approach method. The research method used is a survey method with descriptive and verification approaches, the test instruments used in this study are validity and reliability tests. The data analysis used in this research is multiple regression analysis, the coefficient of determination, and hypothesis testing. The results showed that brand image has a positive and significant effect on purchasing decisions, and store atmosphere has a positive and significant effect on purchasing decisions.